The Quality of Digital Library Services at Alma Ata University, Yogyakarta - Yenny Dwi Artini; Rita Agustina (Institute of Computer Science (IOCS), 2022)
Digital library is a type of library that uses information and communication technology in its services. This is to meet the high level of public needs in accessing information in the globalization era. Digital libraries generally provide both online and offline services. Due to their strategic functions, it is crucial to know how digital libraries, especially those in universities, provide quality services so that educational goals can be achieved. This research examined the quality of digital library services using the LibQUAL+TM method with 4 measurement dimensions, namely Service Affect-SA, Library as Place-LP, Personal Control-PC, and Information Access-IA. The research was carried out with a qualitative descriptive method through interviews, observations, and documentation. The key respondents were selected usingthe purposive sampling technique, and the data were analyzed through 3 stages, namely data reduction, data presentation, and conclusion. The results of the study conclude that the dimensions of Service Affect-SA and Personal Control-PC are good, while the dimensions of Library as Place-LP and Information Access-IA have not been optimal. This shows that the capability to provide optimal services in a digital library does not only require competent human resources and high use of information technologybut also requires the provision of facilities, especially adequate collections of digital collections, and also adequate facilities and infrastructure.